Obstruksi Intestinal akibat Infeksi Ascaris lumbricoides - Avisa Jinan Azura; betta kurniawan; risti graharti (Medula, 2023)
Obstructive ileus or intestinal obstruction is a serious abdominal condition that requires immediate action. One of the causes of obstruction is the presence of a foreign body in the form of the nematode Ascaris lumbricoides. Ascaris lumbricoides infection is a disease that is still widely experienced, especially in children in developing countries. The prevalence of worms in Indonesia has a fairly high range, between 2.5% -62%. Complications in the form of obstructive ileus if not managed can cause death. Intestinal obstruction due to Ascaris lumbricoides can occur when there are many worms, namely more than 60 individuals. This infection is often asymptomatic, but symptoms that often arise are gastrointestinal system disorders such as abdominal pain, nausea, vomiting, and anorexia. Symptoms of obstruction may include vomiting, abdominal distention, increased bowel sounds, darm steifung, darm contour, collapse of the ampulla recti. The initial examination that can be done is in the form of a complete stool examination and abdominal ultrasound to see the presence of worms in the intestine. Management in the form of administering anthelmintic drugs, intestinal decompression using a nasogastric tube, or surgery can be performed.